Analysis of Lapetal Soldiers' Strategy and Competence Related to the Effectiveness of Recruitment of Indonesian Navy Soldiers - Sukmana, Hanny Chandra (Dinasti International Journal of Management Science, 2025)
The recruitment of Indonesian Navy (TNI AL) personnel is a strategic process to ensure the availability of qualified human resources to support maritime defense tasks. This study aims to analyze the strategies and competencies applied by the Naval Personnel Recruitment Agency (Lapetal) to enhance the effectiveness of TNI AL recruitment. Using a qualitative literature-based approach, the study identifies various challenges in the recruitment process, such as uneven geographic distribution of candidates, limited access to information in remote areas, and inadequate outreach efforts. Additionally, strict selection standards add complexity to the recruitment process. The findings reveal that Lapetal’s strategies, including the use of technology in the selection process, pre-selection training programs, and digital media-based outreach, have proven effective in reaching potential candidates from diverse regions. Enhancing recruiter competencies through training and professional certification and publication of the Integrity Pact also plays a key role in ensuring a transparent and accountable selection process. This study highlights the importance of combining innovative strategies and recruiter competencies to ensure the quality of recruited personnel. Recommendations include strengthening outreach efforts, expanding selection coverage in remote areas, improving transparency using data-driven technology and continue recruiter personnel competency program. These steps are expected to help Lapetal further enhance the effectiveness of TNI AL recruitment to support national defense.